26 RESET – the first step in the clinical wellbeing pathway. (23rd February 2023) - Gungor, Jessie; Chan, Sarah; Drake, Gareth; Hothi, Daljit; Bryon, Mandy
Abstract : Background: The COVID-19 pandemic has highlighted the importance of wellbeing support for frontline clinical staff. The newly introduced Great Ormond Street Hospital (GOSH) Clinical Wellbeing Pathway aims to provide consistent support to clinical teams following challenging or distressing events at work. RESET is the initial step in this pathway. It is a brief, facilitated conversation between clinical team members, taking place during the shift in which the clinical event has occurred. 'RESET' is an acronym that encompasses five key themes: Recognise, Evaluate, Stuff still to do, Elevate staff, Taking things forward. Method: We used an action research methodology, where the design and clinical outcomes were co-created with the relevant staff groups. This comprised of an e-survey on existing clinical practices, expert consultation, facilitator training and pilot with ongoing qualitative feedback from staff on two pilot wards. Results: Limited responses from our E-survey on existing hot debrief practices at GOSH highlighted that debriefs did not occur consistently but when they did, they were beneficial. Respondents indicated that training on facilitating debriefs would be well received. Feedback from the expert consultation (n= 14) highlighted the impact of terminology on clinical staff. Therefore, the language of the acronym was adapted accordingly. Feedback also highlighted the important role of the RESET facilitator, being able to respond flexibly and organically to the uncertain and potentially emotive conversations. Preliminary feedback from two facilitator training sessions with senior clinical staff (n= 11) identified the RESET tool and facilitator training is beneficial. Conclusion: This phased introduction of the RESET tool has demonstrated that the proforma and accompanying training is viable to assist in the structure of post-event conversations. Clinical impact has yet to be assessed and we continue to pro-actively gather feedback on the utility and barriers to RESET conversations throughout our ongoing pilot study.